2000
DOI: 10.1590/s0100-40422000000400011
|View full text |Cite
|
Sign up to set email alerts
|

Compostos de mercúrio. Revisão de métodos de determinação, tratamento e descarte

Abstract: Recebido em 31/3/99; aceito em 11/2/00 MERCURY COMPOUNDS. REVIEW ON DETERMINATION, TREATMENT AND DISPOSAL METHODS. This review article on mercury compounds deals with the differences on toxicity of different forms of this metal, the Brazilian regulation for its disposal and the usual methods of determination. Besides that, the text gives special emphasis on the methods used for the treatment and disposal of residues containing mercury, as well as the new developments being made in this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
45

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 17 publications
(36 reference statements)
0
23
0
45
Order By: Relevance
“…8 Other anthropogenic contribution occurs through prospecting, the electrolytic production of chlorine-soda, and the use of fossil fuels, waste incinerators, pigments, pesticides, mercury vapor lamps, batteries, and dental products. 9 All Hg compounds have high toxicity indexes concerning living organisms with organic Hg species being the most toxic. 10 Mercury occurs naturally with other elements, mainly sulfur, forming the cinnabar mineral (HgS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Other anthropogenic contribution occurs through prospecting, the electrolytic production of chlorine-soda, and the use of fossil fuels, waste incinerators, pigments, pesticides, mercury vapor lamps, batteries, and dental products. 9 All Hg compounds have high toxicity indexes concerning living organisms with organic Hg species being the most toxic. 10 Mercury occurs naturally with other elements, mainly sulfur, forming the cinnabar mineral (HgS).…”
Section: Introductionmentioning
confidence: 99%
“…Other natural Hg sources are volcanic eruptions, natural evaporation, and Hg mines. 9 Mercury determination in sediments is a useful tool to evaluate the impact in the aquatic environment. In some studies, 8,[11][12][13][14][15] Hg determination in sediment samples showed levels above of those allowed by the Brazilian legislation (0.17 µg g -1 ), according to level 1 from 2004 CONAMA Resolution 344 (Conselho Nacional do Meio Ambiente).…”
Section: Introductionmentioning
confidence: 99%
“…Devido a esse processo de emissão e reemissão dificulta a descrição exata do movimento do mercúrio a partir de suas fontes (OGA et al, 2008). Para que não haja esta remissão, o descarte mais recomendado é encapsulamento por vitrificação, uma vez que esta técnica reduz as emissões de mercúrio para o meio ambiente (MICARONI et al, 2000).…”
Section: Arsêniounclassified
“…Um dos contaminantes químicos de maior relevância para a saúde pública, relacionado ao consumo de pescado, é o metal mercúrio (Hg), em função da sua toxicidade, do poder acumulativo, pelas altas taxas de absorção e pequenas taxas de excreção pelo organismo. Outro fator que estimula as pesquisas desse metal em organismos marinhos é que o maior influxo desse elemento para o ser humano se dá a partir do consumo de peixes (Micaroni et al, 2000;Ravichandran, 2004;Bisinoti e Jardim, 2004;Marsico et al, 2007 (Faria, 2003). Vários estudos demonstram a ação nociva dos metais pesados no organismo, porém somente o mercúrio está relacionado às intoxicações ocasionadas pelo consumo de pescado e de seus derivados.…”
Section: Introductionunclassified